2002
DOI: 10.1034/j.1600-0544.2002.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial base changes following coronal suturectomy in craniosynostotic rabbits

Abstract: It has been suggested that surgical release of synostosed sutures may ameliorate various cranial base abnormalities in craniosynostotic patients. The present study was designed to test this hypothesis in a rabbit model with familial coronal suture synostosis (CSS). Data were collected from 56 New Zealand White rabbits: 32 unaffected controls, 11 with unoperated CSS, and 13 with CSS released by suturectomy performed at 25 days of age. Serial radiographs were taken at 25, 42 and 84 days. Linear, angular and tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…On the other hand, Mooney et al 12 and Putz et al 13 demonstrated changes in the cranial base and in intracranial pressure when suturectomies were performed in synostotic rabbits. This observation is essential for the understanding of skull behavior when subjected to expansion, since in addition to the expansor force exerted by the springs, the effect is strengthened by increased intracranial pressure, which enables ossification to take place once it is stabilized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Mooney et al 12 and Putz et al 13 demonstrated changes in the cranial base and in intracranial pressure when suturectomies were performed in synostotic rabbits. This observation is essential for the understanding of skull behavior when subjected to expansion, since in addition to the expansor force exerted by the springs, the effect is strengthened by increased intracranial pressure, which enables ossification to take place once it is stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric measurement methods are not comparable 13 , and therefore comparison among different studies are not possible. However, conclusions of a specific project may be valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mooney et al ) and Putz et al (Putz, Smith et al 2001) demonstrated that changes in the cranial base in intracranial pressure occur when synostotic rabbits underwent suturectomy. This is a key observation to understand skull behavior subjected to expansion because in addition to the expansile force exerted by springs, their effect is strengthened through altered intracranial pressure, which when stabilized probably accelerates the ossification process through ceasing the tensile action on bone edges.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits have been widely used as experimental model in studies of behavior of cranial sutures, intracranial pressure, craniometric variations, evolution of fixation materials, and distraction of craniofacial structures (Mabbutt and Kokich 1979;Persson, Roy et al 1979;Alberius and Selvik 1983a;Alberius, Selvik et al 1986;Persing, Babler et al 1986;Alberius, Malmberg et al 1990;Smith, Mooney et al 1996;Singhal, Mooney et al 1997;Losken, Mooney et al 1998;Mooney, Siegel et al 1999;Wendy, Fellows-Mayle et al 2000;Gewalli, Guimaraes-Ferreira et al 2001;Putz, Smith et al 2001;Abreu 2002;David, Gewalli et al 2002;Gosain, Santoro et al 2002;David, Proffer et al 2004;Guimarães-Ferreira, Miguéns et al 2004;Cooper, Singhal et al 2006;Cardoso, Cançado et al 2007;Davis, Windh et al 2008;Davis, Windh et al 2009). Cerebral growth curve of rabbit specimens is similar to those of newborn human children: craniofacial growth in rabbits is accelareted immediately after birth, progressively decreasing from two to thirty-four weeks of age (Alberius, Selvik et al 1986;Abreu 2002).…”
Section: Discussionmentioning
confidence: 99%